Micellization of sodium dodecyl sulphate in the presence and absence of potassium sulphate and nickel sulphate - Mitruka, Jay Narayan; Ojha, Keshab; Bhattarai, Arush; Nepal, Sadiksha; Bhattarai, Ajaya (BIBECHANA, 2022)
The effect of addition of salts on the micellization of anionic surfactant sodium dodecyl sulphate (SDS) in aqueous medium has been studied by conductance measurement at 298.15 K. The critical micelle concentration (CMC) as well as thermodynamic properties was evaluated. From the premicellar and postmicellar slopes, the degree of dissociation (α) of SDS was also calculated. On adding the salts, CMC decreased whereas degree of dissociation increased.  Employing these CMC and α values, the standard free energy of micellization was also evaluated. The negative values of  was decreased when K2SO4 was added but increased when NiSO4 was added.BIBECHANA 19(2022)195-200